Data processing services (MENA Report, 2014)
Contractor name : B.V. ALGEMEEN NEDERLANDS PERSBUREAU ANP Electronic access to information: https://www.tenderned.nl:443/tenderned-web/aankondiging/detail/samenvatting.xhtml?aankondigingId=29487 (c) 2014 Al Bawaba (Albawaba.com)